Impact of Double Barrel Plan on the Crime Rate - Virgelio M. Alao; Naha Marie T. Bañoc (Journal of Research and Multidisciplinary, 2021)
Nowadays, developing countries like Philippines are experiencing inevitable crime problems. The country, Philippines, has been very active in developing methods to reduce if not eradicate the crime rate. One of such methods is called the Double Barrel Plan (DBP) which is an enforcement on the war on drugs. This study evaluated the impact of the DBP on reducing the index and non-index crime rate under quasi-experimental conditions. Quasi-experimental used were single group pre- and post-test design and interrupted time series design. The impact indicators used were the index crime rate and non-index crime rate. Results showed that crime rate after the implementation of the DBP is significantly lesser than the crime rate before the implementation of the DBP for index and non-index crimes using Wilcoxon signed-ranks test. However, using interrupted time series design in the groups studied, DBP has no definite effect on reducing those type of crimes. Nevertheless, the DBP did succeed in reducing the index and non-index crime rate in a specific location of the Philippines. Hence, the DBP has an impact on the reduction of index and non-index crimes.